Gender & Psychoanalysis : an interdisciplinary journal. (Madison : International Universities Press, 1997)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : 59 Boston Post Road, PO Box 1524, Madison CT 06443-1524
Engels
Periodiek